Analysis of the Role of Quality on Job Satisfaction in Management with Sampling Techniques - Murtiarso, I Bagus Hernu; Graha, Yuliana Isma; Alnabawi, Niko (APTISI Transactions on Management (ATM), 2018)
Basically in each management at the College has rules and procedures for writing a study, including in using the research population and sampling techniques to ensure its accuracy. In this study discusses the notion of population and the types of population in a study, sampling units and framework for sampling in Educational research, sample concepts along with the types of sampling, and complete reasons for using sampling and conducting census research. , various sampling methods that will be described as both probability sampling and non probability sampling, as well as explaining the reasons for determining the number of samples both theoretically and practically. So that with the existence of research on the population of research and sampling techniques with examples in the scope of management, it is expected that the samples used in this study actually represent the existing population so that the findings and conclusions obtained from the sampling are valid. Keywords: Research Population, Sampling Technique, Probability and Non Probability